Hippocampus guttulatus diet based on DNA metabarcoding - Tamara, Lazic; Fosso, Bruno; Bachir, Balech; Giuseppe, Corriero; Michele, Gristina; Marinella, Marzano; Graziano, Pesole; Monica, Santamaria; Pierri, Cataldo (Frontiers in Marine Science, 2023)
Seahorses are small sedentary fish considered flagship species of the conservation efforts. They are particularly vulnerable to human pressures because inhabiting threatened coastal ecosystems. Indeed, the worldwide decline of local populations in the last decades led to the inclusion of all seahorse species on the IUCN Red List, where most species, including Hippocampus guttulatus, were classified as ‘‘Data Deficient’’ on a global level due to the lack of relative data on several biological and ecological traits. Because of such sensitive conservation status, improvement of the current knowledge on the diet composition of wild animals and its differences among habitats could be of great importance as it could help understanding the way the environment is exploited. In the present study, we used a non-invasive DNA metabarcoding technique to further elucidate long-snouted seahorse diet and expand our understanding of prey choice among different habitats. We identified 24 families, 22 genera and 26 species, and according to the results, most of the seahorse samples contained taxa such as Amphipoda, Decapoda, Isopoda, and Mysida. Several non-native species were discovered in the diet, suggesting their dietary incorporation that could mirror high anthropogenic impacts and habitat modifications. We found significant differences in the diet composition among investigated habitats, thus indicating trophic flexibility of H. guttulatus among diverse habitats, a characteristic that may be essential for the resilience of this iconic yet sensitive species.